Being human in the shadow of racism - Kuvuna, Joël Mbongi; von Sinner, Rudolf (Stellenbosch Theological Journal, 2018)
This paper is inspired by the experience of a black student who underwent racist treatment in Brazil. Nowadays, racism may appear in any societal structure. Misuse of power is one of the causes of violence and racism. A person who finds him- or herself in a position of some power may, while acting in the name of “law”, turn into an incarnation of the law. This paper wishes to speak out on matters of violence, oppression and racism which are spreading in society. The faces of racism need to be shown, even where racism is institutionalized.